The Application of SECI Method as a Learning Innovations in Rural Areas - Juwarti; Nureeda Waena; Agci Hikmawati (International Journal of Learning Reformation in Elementary Education, 2022)
In various regions, educators always expect to be able to run education well, which complete facilities support. However, this expectation is not always fulfilled, especially in schools in the interior both Indonesia and Thailand. Learning in rural areas is always constrained by the lack of facilities owned, causing the material not to be delivered properly. The purpose of this study was to reveal how learning in rural areas applied the SECI method. There are many learning resources from the surrounding nature focusing on the activeness of students and giving rewards. The results of this study show that there is optimism for good learning in the interior even though there are limited existing facilities by innovating to utilize learning resources from around the school that is easy to obtain.